2019
DOI: 10.1017/s0954579419000798
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of parenting interventions in foster care and adoption

Abstract: Foster and adoptive parents often face challenges while taking care of children who, due to their adverse early life experiences, are at risk of developing insecure attachment relationships, behavior problems, and stress dysregulation. Several intervention programs have been developed to help foster and adoptive parents to overcome these challenges. In the current study, a series of eight meta-analyses were performed to examine the effectiveness of these intervention programs on four parent outcomes (sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 128 publications
(177 reference statements)
5
45
1
2
Order By: Relevance
“…The finding that positive parenting is predictive of foster children's prosocial behavior is hopeful because it could indicate that foster parents can boost their foster children's development through positive parenting. This is a reassuring finding and in line with the positive effects of intervention programs on parent outcomes and child problems (Schoemaker et al 2019).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The finding that positive parenting is predictive of foster children's prosocial behavior is hopeful because it could indicate that foster parents can boost their foster children's development through positive parenting. This is a reassuring finding and in line with the positive effects of intervention programs on parent outcomes and child problems (Schoemaker et al 2019).…”
Section: Discussionsupporting
confidence: 69%
“…Previous research showed that foster children's challenging behaviors are perceived as very stressful by foster parents and contribute most to their stress levels (McKeough et al 2017). A recent meta-analysis shows promising effects of foster care interventions on parenting stress (g = 0.60) and foster children's behavior problems (g = 0.53) (Schoemaker et al 2019). Our study pointing out foster parent stress as a key factor related to foster children's mental health, the promising findings of the metaanalysis of Schoemaker et al (2019) regarding the efficacy of interventions in reducing foster parent stress, and the fact that foster parents themselves express a desire for additional training (McKeough et al 2017) should provide a clear signal to policymakers and professionals to improve foster parent support and training for better placement outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Available research suggests that attachment-based interventions can be effective in increasing foster parents' sensitivity to their foster children's signals (Bick & Dozier, 2013;Dozier et al, 2009), and facilitate positive fosterchild development in a number of ways (Bernard et al, 2017;Dozier et al, 2008;Lind et al, 2017). However, it should be noted that research has thus far not been able to show that such interventions alone reduce placement disruption (Schoemaker et al, 2019).…”
Section: The Value Of Continuity Of "Good-enough" Carementioning
confidence: 99%
“…For virtual visits to be successful, training of social workers, foster parents and birth parents may be necessary. Training programs for foster parents have been effective in decreasing placement disruptions (Price et al, 2008, Schoemaker et al, 2019 and improving a foster parent's ability to work with children with disruptive behavior problems (Solomon et al, 2016). Recently, Mallette et al (2020) examined the supports necessary for foster parents to be successful in coordinating their interactions with the social welfare system, the child in their care and with birth parents.…”
Section: Implications For Case Planning and Implementationmentioning
confidence: 99%